EFEKTIFITAS MODEL LEARNING CYCLE 5E BERBANTUAN MEDIA KOMIK DITINJAU DARI GAYA BELAJAR - Cahyaning Tyas Putri Utami; Rita P. Khotimah; Sri Rejeki (Jurnal Pembelajaran Matematika, 2018)
Abstract: LC 5E model is a learning model centered on students who direct students to learn gradually starting from engagement, exploration, explanation, elaboration, and evaluation. This study aims at testing: (1) the effects of the 5E LC model and LC 5E -assisted comic media towards students' learning outcomes. (2) the effects of students' learning styles on students' learning outcomes. (3) the effects of interaction of learning models and students' learning styles on students' learning outcomes. This is a quantitative research with the quasi-experimental design. The data collection techniques used in this study test, questionnaire, and documentation. The data were analyzed using analysis of variance of two different cells with α = 5%. Based on the data analysis, it can be concluded that: (1) there is an effect of the LC 5E model and LC 5E -assisted comic media towards students' learning outcomes. Were students' learning outcomes with LC 5E -assisted comic media are better than those who are treated by LC 5E, 2) there is an effect of students' learning styles towards students' learning outcomes. Based on the test results further of post anava, it can be concluded that students' with visual learning styles have better learning outcomes than those with auditory and kinesthetic learning styles. The learning outcomes of students' with auditory learning styles are as well as the learning outcomes of students' with kinesthetic learning styles, and (3) there are no effects of interaction of learning models and learning styles of students towards students' learning outcomes.Keywords: Comic, LC 5E, Learning Styles.